Innovative Development of a Modern University in The Conditions of The Digitalization of Education " - Baibayeva Muhayo Khudaibergenovna; Asadova Shahlo Rakhmatilla qizi (Genius Journals, 2022)
This paper analyses the use of digital technology-based education innovations in higher education. It is shown that extensive implementation of digital technologies in universities is the main factor conditioning the acceleration of innovative changes in the education process, while digital technologies themselves become one of the key mechanisms for creating the competitive advantages of education institutions on the market of educational services. The analysis of the application of digital technology-based education innovations in higher education enabled the authors to develop a layer model of assessing the readiness of universities to implement digital technologies, presented as a unity of three interrelated criteria determining the readiness of universities for the use of digital technologies in the education process: organisational and methodological, technological, and professional.
Keywords: Innovations; University; Digital Technology; Information